Optimizing weld strength and microstructure in CP-titanium and 304 stainless steel friction welds with chromium interlayer - Mohammad Mostafa Sheykhi; Mohammad Ali Mostafaei (Results in Materials)
This study investigates the effect of a Cr-interlayer on the hardness and friction-welded joint strength between CP-titanium and 304 stainless steel. Rotary friction welding, with its adjustable parameters such as upset pressure, is the preferred method for this dissimilar joint. Due to the difference between these two base metals, a metallic interlayer like chromium, is crucial for controlling the formation of intermetallic compounds (IMCs). Welding was conducted at three different upset pressures, both with and without the Cr-interlayer. Tensile and microhardness tests were performed, complemented by phase analysis and microstructural characterization using XRD and SEM. Our findings reveal that employing a chromium layer and higher upset pressures enhances strength while reducing the presence of brittle IMCs in the welds. At the CP-titanium side, dynamic recrystallization occurs due to increased heat generation at the interface and strain occurred by materials flow, facilitating IMC formation, especially evident at 250 MPa upset pressure. Interestingly, relatively higher strength at 150 MPa is attributed to the absence of IMCs. Conversely, higher strength results at 350 MPa due to from the flow of softened material, effectively purging IMCs from the weld zone. Notably, both β-titanium and chromium-based IMCs form in the presence of the chromium interlayer, resulting in decreased joint hardness and increased overall ductility. In conclusion, our study's findings contribute to bridging the gap between theoretical strength and practical application, significantly advancing joint performance.